Digital Maps and Senses of Security: The Influence of a Veracious Media on Urban Life - Matthew S. Hanchard (Urban Planning, 2020)
Digital technologies mediate our experience and use of urban space in several ways. This article argues that people trust the information provided by digital maps (such as Google Maps, Bing Maps, and OpenStreetMap), including datasets embedded within them, e.g., crime statistics and council tax banding. People choose particular sites and routes, and they make wider decisions based on digital map content. The article highlights the senses of security people gain from using digital maps, and the influence that their use has, for instance, on choices of which home to buy (landed capital acquisition), which route to take and by which mode of transport, and which restaurant or hotel to visit. As such, the article argues that digital maps influence the ways in which bodies are distributed and move in urban space. The article applies a practice theory lens to data from a scoping sample survey (n = 261), 32 semi-structured interviews, and three focus groups. Through empirical examples, it demonstrates how a sense of security provided by digital maps is experienced by users, and how that serves to influence the decisions people make in negotiating and making urban space meaningful.